IMPLIKASI TERHADAP PENGUJIAN KETETAPAN MPR/MPRS PASCA PUTUSAN MAHKAMAH KONSTITUSI DALAM RANGKA MENGAWAL TEGAKNYA KONSTITUSI NEGARA - Tomi Agustian (Universitas Bengkulu, 2017)
This study aims: first, the decision of the Constitutional Court adjudicates and does not accept the testing of the MPR Decree, secondly, the implications of testing the MPR's Decree after the decision of the Constitutional Court. The method used in this study is normative research or library research. The results of the study obtained first, the basis of the Constitutional Court Decision according to the 1945 Constitution of 24C paragraph (1) that the Constitutional Court only has the authority to test the Law on the Basic Law and the MPR / S Decree is not included in the Constitutional Court's authority. Secondly, the implication is that there is no mechanism for testing. MPR provisions cause a legal vacuum as well as the absence of an authorized institution to test the MPR Decree (tetraa incognita)